2021
DOI: 10.1177/00048674211068788
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the effectiveness of repetitive transcranial magnetic stimulation treatment in depression, again

Abstract: Following on from the publication of the Royal Australian and New Zealand Journal of Psychiatry Mood Disorder Clinical Practice Guidelines (2020) and criticisms of how these aberrantly addressed repetitive transcranial magnetic stimulation treatment of depression, questions have continued to be raised in the journal about this treatment by a small group of authors, whose views we contend do not reflect the broad acceptance of this treatment nationally and internationally. In fact, the evidence supporting the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Regarding associated treatment, there is growing evidence that concomitant use of medication can impair the clinical effectiveness of rTMS, especially for benzodiazepines ( 57 ). However, the impact of concomitant medication on rTMS effectiveness is still debatable ( 58 , 59 ). Finally, we did not find a link between baseline RMT and response.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding associated treatment, there is growing evidence that concomitant use of medication can impair the clinical effectiveness of rTMS, especially for benzodiazepines ( 57 ). However, the impact of concomitant medication on rTMS effectiveness is still debatable ( 58 , 59 ). Finally, we did not find a link between baseline RMT and response.…”
Section: Discussionmentioning
confidence: 99%
“…Each participant was evaluated by a professionally trained psychiatrist using the Hamilton depression scale (HAMD). The scores were categorized as no depression (0-7), mild depression (8)(9)(10)(11)(12)(13)(14)(15)(16), moderate depression (17)(18)(19)(20)(21)(22)(23), and severe depression (≥24) [25].…”
Section: Hamilton Depression Scale (Hamd)mentioning
confidence: 99%
“…First, the comparative efficacy of rTMS has been documented in a network meta-analysis (notably published by authors from the pharmaceutical industry) which found that rTMS produced either the equal best or clearly best outcomes on response and remission rates after 4 and 6 weeks of treatment compared to all other interventions for treatment-resistant depression (TRD): clear evidence of 'comparative efficacy' (Papadimitropoulou et al, 2017). The overall efficacy of rTMS has been explored although in a more limited set of studies than the vast (over 50) randomised trials (see among other studies, Brunoni et al, 2017;Razza et al, 2020) which have confirmed that it is an effective intervention when compared to sham (Fitzgerald et al, 2021). These sham-controlled studies of rTMS in patients who have failed two or more medications show that active treatment results in superior outcomes to those reported at the equivalent third or fourth levels in the STAR*D trial.…”
Section: To the Editormentioning
confidence: 99%
“…No attempt has been made to address the considerable body of evidence presented in previous articles addressing these claims (e.g. Fitzgerald et al, 2021) or to provide a balanced or systematic review of the actual evidence. These claims and evidence-based rebuttals are presented in Table 1.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation